Ascorbic Acid for the Prevention of Contrast‐Induced Nephropathy After Coronary Angiography in Patients With Chronic Renal Impairment: A Randomized Controlled Trial. Issue 4 (11th August 2013) - Dvoršak, Benjamin; Kanič, Vojko; Ekart, Robert; Bevc, Sebastjan; Hojs, Radovan
Abstract To determine the incidence of contrast‐induced nephropathy (CIN) and to assess the effectiveness of ascorbic acid in the prevention of CIN after coronary angiography in patients with chronic renal impairment. CIN is the third most common cause of hospital‐acquired renal failure. It is well documented that periprocedural hydration is effective in the prevention of CIN. Little data exist on the effectiveness of ascorbic acid, a vitamin with antioxidative action. Patients with stable serum creatinine level >107 μmol/L (n = 81) undergoing coronary angiography were randomized to receive either ascorbic acid (N = 40) or placebo (N = 41) before the procedure. All patients received intravenous volume expansion with normal saline before the procedure. CIN was defined as an increase of serum creatinine level >25% from baseline measured 3 to 4 days after the procedure. CIN occurred totally in 5/81 patients (6.2%); in two patients (3%) in the ascorbic acid group and in three patients (7.3%) in the placebo group (P = 0.512). Postprocedural worsening of renal function (postprocedural increase of serum creatinine level) was present in 10/81 patients (12.3%) in the ascorbic acid group and in 19/81 patients (23.4%) in the placebo group (P = 0.038). No patient required dialysis treatment. We found no statistically significant impact of ascorbic acid on the incidence of CIN in patients with chronic renal impairment undergoing coronary arteriography or angioplasty. Ascorbic acid may still have some protective role in CIN reflected in lower incidence of worsening of renal function in the treated group.